2010
DOI: 10.1038/hr.2010.114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dysregulation of glucose metabolism with white-coat hypertension: the Ohasama study

Abstract: Characteristics of glucose metabolism in subjects with white-coat hypertension (WCHT) have not been fully investigated. The purpose of this study was to determine the relationship between glucose metabolism and WCHT on the basis of blood pressure (BP) at home (HBP) in the general population. Participants were from Ohasama, a rural Japanese community, and included 466 residents (mean age, 61.0 years) who had no history of diabetes mellitus. HBP and oral glucose tolerance test values were measured. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…These findings suggest that WCHT is associated with glucose dysregulation and an increased risk for diabetes [18,19] . Therefore, WCHT is an initial sign of deteriorating health.…”
Section: Metabolic Syndromementioning
confidence: 75%
“…These findings suggest that WCHT is associated with glucose dysregulation and an increased risk for diabetes [18,19] . Therefore, WCHT is an initial sign of deteriorating health.…”
Section: Metabolic Syndromementioning
confidence: 75%
“…The prevalence of impaired glucose tolerance was 24.4% and 17.2% in the WCHT and normotensives, respectively, whereas the prevalence of diabetes was 8.9% and 3.7% normotensives, respectively. 13 A link between impaired glucose tolerance and WCHT was also found in a study of 105 subjects who were aged 39-75 years, untreated, non-smokers and with normal fasting glucose levels. 14 Mean 2 h plasma glucose level post-load, adjusted for age and waist circumference, was 5.7 mmol/L in normotensives and 7.4 mmol/L in the WCHT group (P = 0.002).…”
Section: Is White-coat Hypertension Associated With Metabolic Syndrome?mentioning
confidence: 75%
“…The prevalence of impaired fasting glucose was 11.1% and 2.2% in the WCHT and normotensives, respectively. The prevalence of impaired glucose tolerance was 24.4% and 17.2% in the WCHT and normotensives, respectively, whereas the prevalence of diabetes was 8.9% and 3.7% normotensives, respectively …”
Section: Is White‐coat Hypertension Associated With Metabolic Syndrome?mentioning
confidence: 91%
“…It was reported that WCH was accompanied by a greater proportion of other cardiovascular risk factors, such as impaired glucose metabolism, high BMI, and dyslipidemia [27,29,30], which were also known as risk factors for CVD. In our study, most of the included studies were adequately adjusted for these risk factors.…”
Section: Discussionmentioning
confidence: 99%